Investigating the parts to understand the whole : contribution of phenolic compounds to the desired estrogenic activity of SM6Met fractions from Cyclopia subternata - Claassen, Herzelle (Stellenbosch :Stellenbosch University, 2018)
Thesis (MSc)--Stellenbosch University, 2018.